Cryptocurrencies and cryptoassets : regulatory and legal issues - Haynes, Andrew, 1953-; Yeoh, Peter (Abingdon, Oxon ; New York, NY : Informa Law from Routledge, 2020)
"This book examines the legal and regulatory aspects of cryptocurrency and blockchain and the emerging practical issues that these issues involve. The analysis covers a range of advanced economies across the world, in America, Europe and Asia. The book describes, explains and analyses the nature of cryptocurrencies and the blockchain systems they are constructed on in these major world economies and considers relevant law and regulation and their shortcomings. It will be of use and interest to academics, lawyers, regulators and anyone involved with cryptocurrencies and blockchain"--
Introduction -- Cryptocurrencies : Opportunities and Risks -- Digital Global Currency -- Why are the Regulators Watching? -- Global Cryptoasset Hubs -- Cryptoasset Policies of International Bodies -- Cryptoasset Regulataory Policies in Selected Western Economies -- Cryptoasset Policies in Selected Asian Economies -- Distributed Ledger Technology -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Cryptocurrencies -- Law and legislation; LAW / Banking; LAW / Computer & Internet; LAW / Administrative Law & Regulatory Practice